Satellite-Detected Anomalous Changes in Parameters of Various Geophysical Fields During Earthquakes of 6 ≤ M ≤ 7.8 in Türkiye in February 2023 - Bondur Valeriy; Tsidilina Marina; Efremycheva Elena; Voronova Olga; Gaponova Mariya; Feoktistova Natalya; Zima Alla (Russian Journal of Earth Sciences, 2024)
Research was conducted using satellite data to study variations in parameters of various geophysical fields manifested in the lithosphere, atmosphere, and ionosphere during the preparation and occurrence of destructive earthquakes of 6 ≤ M ≤ 7.8 in Türkiye in February 2023. Precursor manifestations of these seismic events were satellite-detected in the form of anomalies in parameters of various geophysical fields, including: lineament systems, surface skin temperature and surface air temperature, relative humidity, latent heat flux, integrated flux of outgoing longwave radiation, altitude changes in ionospheric electron density, total electron content of the ionosphere, as well as aerosol optical depth. It was found that the anomalies of all studied geophysical fields detected using satellite data manifested most intensively during the period 3–13 days before the onset of seismic events.